Archival irruptions: constructing religion and criminalizing Obeah in eighteenth-century Jamaica - Gerbner, Katharine (Religious cultures of African and African diaspora people, 2025)
"In Archival Irruptions, Katharine Gerbner offers a new method for reading colonial and missionary archives by focusing on "irruptions," moments when marginalized epistemologies break through the narrative field of a Eurocentric archive. Through a microhistory of the Moravian archive from Jamaica, Gerbner shows how scholars can utilize colonial and missionary sources to tell Africana stories. Reading for irruptions offers insight into the Afro-Caribbean practice of Obeah before the practice was deemed a crime. Obeah, which developed in the British Caribbean under slavery, was criminalized as witchcraft by the British colonial government in the wake of Tacky's Revolt, the largest enslaved uprising in the eighteenth-century British Atlantic World. While historians often view Obeah through the lens of European categories such as religion or superstition, reading for irruptions reveals a new story about Obeah, Christianity, and criminalization. Archival Irruptions argues that we must reckon with the legacies of slavery to understand how some religious practices have been, and continue to be, excluded from the lexicon of religion and criminalized. Reading colonial and missionary archives for irruptions offers one method to address the history of epistemic violence and re-center the lives, experiences, and perspectives of those who have been targeted by systemic repression and criminalization"--